Diverse Expression of Antimicrobial Activities Against Bacterial Vaginosis and Urinary Tract Infection Pathogens by Cervicovaginal Microbiota Strains of Lactobacillus gasseri and Lactobacillus crispatus - Atassi, Fabrice; Pho Viet Ahn, Diane L.; Lievin-Le Moal, Vanessa (Frontiers in Microbiology, 2019)
Objectives: We aimed to analyze the strain-by-strain expression of a large panel of antimicrobial activities counteracting the virulence mechanisms of bacterial vaginosis-associated P. bivia and G. vaginalis, pyelonephritis-associated E. coli, and recurrent cystitis- and preterm labor-associated E. coli by L. gasseri and L. crispatus strains resident of the cervicovaginal microbiota of healthy women. Methods: We evaluated the antimicrobial properties of human cervicovaginal microbiota-associated L. gasseri and L. crispatus cells and secreted molecules, focusing on bactericidal and bacteriostatic effects on free, adhering, or internalized pathogens and biofilm disrupting activity; the inhibition of pathogen association with cervix epithelial cells by competition, exclusion, or displacement; and protective properties against the deleterious cellular effects of specific pathogen toxins. Results: We found that no antimicrobial activity is specific to resident L. gasseri or L. crispatus species. Non-strain specific antimicrobial activity was exerted by secreted lactic acid, which killed the microbial pathogens by direct contact. The Lactobacillus cells exhibited another non-strain specific activity which inhibited the association of microbial pathogens with cervix epithelial cells with varying efficiency, partially protecting the cells against lysis and detachment triggered by toxin-producing G. vaginalis and uropathogenic E. coli. Potent strain-specific bactericidal activity was exerted by a limited number of resident L. gasseri strains with the capacity to produce and secrete antibiotic-like compounds. These compounds eradicated the microbial pathogens pre-associated with the surface of cervix epithelial cells, providing efficient protection of the cells against the deleterious effects triggered by toxin-producing G. vaginalis and uropathogenic E. coli. Furthermore, these compounds crossed the cell membrane to kill the pre-internalized microbial pathogens. Conclusion: Our findings show that human microbiota-associated cervicovaginal strains of L. gasseri and L. crispatus share common lactic acid-associated antimicrobial activities. Our results also provide evidence of strain-level specificity for certain antimicrobial properties among cervicovaginal L. gasseri and L. crispatus strains, indicating that the presence of a particular species in the vaginal microbiota is not sufficient to determine its benefit to the host. A full repertory of strain-specific properties should be evaluated in choosing vaginal microbiota-associated Lactobacillus isolates for the development of live biotherapeutic strategies